Biofuelcells-Recent advances and applications - Davis, Frank; Higson, Seamus P. J. (Elsevier, 2007)
In 2006, the journal Biosensors and Bioelectronics published a special issue devoted exclusively to biofuel cells, including several research papers and an extensive review of the field [Bullen, R.A., Arnot, T.C., Lakeman, J.B., Walsh, F.C., 2006. Biosens. Bioelectron.]. Within this review a brief description will firstly be given of the history of biofuel cells together with coverage of some of the major historical advances. The review is intended, however, to largely concentrate on and give an overview of the advances made in recent years in this area together with a discussion surrounding the practical application of biofuel cells. There are several classes of biofuel cells: we shall firstly discuss the recent advances in biofuel cells that convert chemical fuels to produce electrical power by use of catalytic enzymes. This will be followed by a section on similar cells where micro-organisms rather than enzymes are used to convert the fuel to energy. Thirdly we shall consider hybrid biofuel cells that combine the utilisation of photochemical chemistries and biological systems for the generation of electricity. Finally we will discuss some of the proposed uses of biofuel cells together with a short consideration of future research possibilities and applications of these systems.
Keywords: Bioelectronics; Biofuel cells; Glucose oxidase; Microbial fuel cells